EVALUATION OF VIBRIO CHOLERAE 569B INABA PROTECTIVE ANTIGENES, DERIVED ON INDUSTRIAL AND DEVELOPED BIOREACTORS AS WELL AS BY IMPROVED TECHNOLOGY - A. K. Nikiforov; M. N. Kireyev; O. V. Gromova; A. V. Komissarov; S. A. Yeriomin; O. A. Volokh; Yu. A. Aleshina; A. V. Gayeva; T. L. Zakharova; V. I. Pavlova (Acta Biomedica Scientifica)
We evaluated immunochemical, physical and biochemical properties of Vibrio cholerae 569B INABA protective antigenes, derived on industrial and own-developed bioreactors as well as by technology of its concentration by tangential ultrafiltration. We detected, protease, twinase and. lysophospholipase in all samples. Also, dotimmunoanalysis showed equal concentration, of cholerogen-anatoxine and. O-antigen in all samples too. Using chromatography and. electrophoresis, we found their properties as similar. Thus, we suppose to be possible using developed bioreactor as well as technology of Vibrio cholerae 569B INABA protective antigens concentration by tangential concentration during a process of synthetic oral cholera vaccine production.